Variation of lignocellulosic biomass structure from torrefaction: A critical review. (December 2021) - Ong, Hwai Chyuan; Yu, Kai Ling; Chen, Wei-Hsin; Pillejera, Ma Katreena; Bi, Xiaotao; Tran, Khanh-Quang; Pétrissans, Anelie; Pétrissans, Mathieu
Abstract: In recent years, torrefaction, a kind of biomass thermal pretreatment technology, has received a great deal of attention due to its effective upgrading performance of biomass. Recent studies have also suggested that the quality of syngas and bio-oil (or biocrude) from the pyrolysis, gasification, and liquefaction of torrefied biomass can be effectively improved. Torrefaction changes the structure of the biomass, the degree of this change depends strongly on the severity of the torrefaction process. To have a better understanding of the impact that torrefaction has on the biomass structure, this study aims to provide a comprehensive and in-depth review of recent advances on this topic. Particular attention is paid to biomass structure analysis through thermogravimetric analysis, scanning electron microscopy, Fourier transform infrared analysis, Brunauer-Emmett-Teller, X-ray photoelectron spectroscopy, and nuclear magnetic resonance. From these analyses, the thermal degradation characteristics of hemicelluloses, cellulose, lignin, and other components in biomass can be recognized. In addition to the elaboration of biomass structure variation from torrefaction, future challenges and perspectives are also underlined. The insights provided in this review are conducive to the further applications of biomass torrefaction for sustainable biofuel production. Highlights: The impact of torrefaction on lignocellulosic biomass structure is deeply reviewed. Several analyses for figuring out the variation of biomass structure are elaborated. The advantages and limitations of a variety of analyses are illustrated. Future challenges and perspectives of study in this topic are underlined. Biomass structure analysis and understanding are crucial for torrefaction applications.